ANALISIS PENGUNGKAPAN ASPEK SOSIAL BERDASARKAN STANDAR GRI 400 PADA PERUSAHAAN E-COMMERCE DAN FINTECH - latifatun nisa; Agus Bandiyono (Jurnal Riset Akuntansi, 2025)
Abstract: This study aims to analyze the disclosure of social aspects based on GRI standards in an e-commerce and fintech company in Indonesia. The method used is content analysis of the company's sustainability reports from 2021 to 2023. The analysis results indicate that the level of social aspect disclosure is not yet complete and still has room for improvement. The findings show that the disclosure of social aspects in the report is not yet fully comprehensive and can be further developed. This analysis is expected to provide new insights into the implementation of social aspect disclosure in e-commerce and fintech companies. In the future, the government is expected to formulate policies that promote higher transparency in sustainability reporting and strengthen the role of stakeholders in the materiality determination process. Keywords: E-commerce sector; fintech sector; GRI 400; sustainability disclosure